Heat tolerance of reptile embryos: Current knowledge, methodological considerations, and future directions. Issue 1 (5th August 2020) - Hall, Joshua M.; Sun, Bao‐jun
Abstract: Aspects of global change result in warming temperatures that threaten biodiversity across the planet. Eggs of non‐avian, oviparous reptiles (henceforth "reptiles") are particularly vulnerable to warming due to a lack of parental care during incubation and limited ability to behaviorally thermoregulate. Because warming temperatures will cause increases in both mean and variance of nest temperatures, it is crucial to consider embryo responses to both chronic and acute heat stress. Although many studies have considered embryo survival across constant incubation temperatures (i.e., chronic stress) and in response to brief exposure to extreme temperatures (i.e., acute stress), there are no standard metrics or terminology for determining heat stress of embryos. This impedes comparisons across studies and species and hinders our ability to predict how species will respond to global change. In this review, we compare various methods that have been used to assess embryonic heat tolerance in reptiles and provide new terminology and metrics for quantifying embryo responses to both chronic and acute heat stress. We apply these recommendations to data from the literature to assess chronic heat tolerance in 16 squamates, 16 turtles, five crocodilians, and the tuatara and acute heat tolerance for nine squamates and one turtle. Our results indicate that there is relatively large variation in chronic and acute heat tolerance across species, and we outline directions for future research, calling for more studies that assess embryo responses to acute thermal stress, integrate embryo responses to chronic and acute temperatures in predictive models, and identify mechanisms that determine heat tolerance. Abstract : We review methods for calculating heat tolerance of non‐avian reptile embryos and define new metrics that can be used to better compare embryo thermal physiology across studies and species. Highlights: We propose metrics for reptile embryo heat tolerance with respect to chronic and acute temperatures and describe how future studies can incorporate these metrics to advance our understanding of embryo thermal physiology.